2022
DOI: 10.3389/fmolb.2022.805931
|View full text |Cite
|
Sign up to set email alerts
|

Detection of CCR5Δ32 Mutant Alleles in Heterogeneous Cell Mixtures Using Droplet Digital PCR

Abstract: The C-C chemokine receptor type 5 (CCR5 or CD195) is one of the co-receptor binding sites of the human immunodeficiency virus (HIV). Transplantations of hematopoietic stem cells with the CCR5Δ32 knockout mutation could represent an effective tool for the complete cure of HIV; these methods having passed the stage of proof-of-principle. At the same time, using the modern CRISPR/Cas9 genome editing method, we can effectively reproduce the CCR5Δ32 mutation in any wild-type cells. Thus, the task of searching for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…For instance, CCR5 gene-edited primary human CD4 + T cells were found to be resistant to HIV-1 infection in vitro [ 24 , 52 , 53 , 74 ], recapitulating results obtained with other gene editing tools, such as TALENs and zinc finger nucleases [ 75 , 76 ]. Additionally, the CCR5Δ32/Δ32 mutation has been introduced in cell lines and primary human CD4 + T cells via CRISPR [ 51 , 77 ], with no off-target effects detected [ 51 ]. However, while ZFN-mediated CCR5-knockout CD4 + T cells have been shown to persist in vivo [ 76 ], these numbers can decline rapidly.…”
Section: Targeting Ccr5 Via Crispr/cas9-mediated Genome Editingmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, CCR5 gene-edited primary human CD4 + T cells were found to be resistant to HIV-1 infection in vitro [ 24 , 52 , 53 , 74 ], recapitulating results obtained with other gene editing tools, such as TALENs and zinc finger nucleases [ 75 , 76 ]. Additionally, the CCR5Δ32/Δ32 mutation has been introduced in cell lines and primary human CD4 + T cells via CRISPR [ 51 , 77 ], with no off-target effects detected [ 51 ]. However, while ZFN-mediated CCR5-knockout CD4 + T cells have been shown to persist in vivo [ 76 ], these numbers can decline rapidly.…”
Section: Targeting Ccr5 Via Crispr/cas9-mediated Genome Editingmentioning
confidence: 99%
“…Knockout confers in vitro resistance to HIV infection in differentiated macrophages [74] Multi-lineage differentiation in vitro [53] Minimal off-target modifications detected Multi-lineage engraftment potential in animal model [82] Multi-lineage engraftment potential in animal model In vivo resistance to HIV infection [57] Multi-lineage engraftment potential after autologous HSC transplantation Persistence of low frequencies of CCR5 knockout CD4 + T cells [66] iPSCs No off-target modifications detected iPSC-derived monocytes/macrophages resistant to HIV infection [83][84][85] Primary CD4 + T cells Low transduction efficiency with lentiviral vectors [52] Knockout confers in vitro resistance to HIV infection [24,52,53,74] Introduction of ∆32/∆32 mutation No off-target modifications detected [51] Macrophage or T cell cell-lines CRISPR-mediated KO feasible [78,86,87] Introduction of ∆32/∆32 mutation High fidelity screening method [77] This was expanded upon by Xu et al, where also in an in vivo animal model resistance to HIV infection was observed after CCR5-knockout HSC engraft generated via CRISPR/Cas9 [57]. As discussed, autologous CRISPR-edited CCR5 knockout HSCs have also been successfully transplanted in a patient with HIV and acute lymphocytic leukemia [66].…”
Section: Hscsmentioning
confidence: 99%